A potential new pathway for heparin treatment of sepsis-induced lung injury: inhibition of pulmonary endothelial cell pyroptosis by blocking hMGB1-LPS-induced caspase-11 activation - Yang, Rui; Zhang, Xiaojuan (Frontiers in Cellular and Infection Microbiology, 2022)
Sepsis is a significant cause of mortality in critically ill patients. Acute lung injury (ALI) is a leading cause of death in these patients. Endothelial cells exposed to the bacterial endotoxin lipopolysaccharide (LPS) can progress into pyroptosis, a programmed lysis of cell death triggered by inflammatory caspases. It is characterized by lytic cell death induced by the binding of intracellular LPS to caspases 4/5 in human cells and caspase-11 in mouse cells. In mice,caspase-11-dependent pyroptosis plays an important role in endotoxemia. HMGB1 released into the plasma binds to LPS and is internalized into lysosomes in endothelial cells via the advanced glycation end product receptor. In the acidic lysosomal environment, HMGB1 permeates the phospholipid bilayer, which is followed by the leakage of LPS into the cytoplasm and the activation of caspase-11. Heparin is an anticoagulant widely applied in the treatment of thrombotic disease. Previous studies have found that heparin could block caspase-11-dependent inflammatory reactions, decrease sepsis-related mortality, and reduce ALI, independent of its anticoagulant activity. Heparin or modified heparin with no anticoagulant property could inhibit the alarmin HMGB1-LPS interactions, minimize LPS entry into the cytoplasm, and thus blocking caspase-11 activation. Heparin has been studied in septic ALI, but the regulatory mechanism of pulmonary endothelial cell pyroptosis is still unclear. In this paper, we discuss the potential novel role of heparin in the treatment of septic ALI from the unique mechanism of pulmonary endothelial cell pyroptosis.